Prediction of eigenmodes cutoff frequencies of sectoral coaxial ridged waveguides - Dubrovka, Fedor; Piltyay, Stepan (Видавництво Львівської політехніки, 2012)
A mathematical model of sectoral coaxial ridged waveguides has been developed using coupled-integralequations technique. Maximal ratios of cutoff frequencies of two lowest modes of sectoral coaxial ridged waveguides have been obtained.
Keywords: Sectoral coaxial ridged waveguide; Coupledintegral-equations technique; Cutoff frequency